Methodological Problems: testimonies and repression - Janotti, Maria de Lourdes Monaco (Cadernos CERU, 2001)
In only years of existence, the School of Application of USP, renewed public school and quality, he/she acquired reputation of being one of the principal centers of the critical teaching in the country. In 1967 there were deep disagreements between the School and FFCL, lacerated internally. They were, then, expelled by the police and agents of DOP, with the connivance of the academical authorities. Under the repressive climate of the military dictatorship, the student´s of CA reaction took wide proportions. Students and teachers were annotated, interrogated and arrested by DOPS. FFCL installed and investigation commission on those events. Starting from then, the School of Application agonized up to 1969, when FFCL stamped your end, turning of your memory. This article compared the two teacher´s depositions rendered in 1967 to the Commission, with the interviews orals the granted after thirty years on the same events. Of that comparison it resulted a series of reflections about history and memory.